2017
DOI: 10.1080/14786419.2017.1392948
|View full text |Cite
|
Sign up to set email alerts
|

Iridoid glycosides and polyphenolic compounds from Teucrium chamaedrys L.

Abstract: In this work, the phytochemical analysis of Teucrium chamaedrys L. collected in Italy was reported. Eight compounds were isolated and identified by means of classical column chromatography and spectroscopic techniques, such as NMR and MS. In detail, these compounds were: verbascoside (1), forsythoside b (2), samioside (3), alyssonoside (4), harpagide (5), 8-O-acetyl-harpagide (6), cirsiliol (7) and β-arbutin (8). The presence of these compounds, in particular iridoids and phenyl-ethanoid glycosides, has a chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 48 publications
(6 reference statements)
0
24
0
Order By: Relevance
“…More specifically, the phenylethanoid glycosided have a chemotaxonomical relevance when in co-occurrence with iridoids [97]. This was already observed in several species comprised in the Lamiales order [98][99][100][101][102][103] as well as in the case of several Pedicularis spp.Also within the same family which Pedicularis genus belong to (Orobanchaceae), these compounds are extremely common and, in fact, they have been already reported in several genera such as Orobanche L., Cistanche L. and Orthocarpus Nutt. [104].…”
Section: Chemotaxonomymentioning
confidence: 66%
“…More specifically, the phenylethanoid glycosided have a chemotaxonomical relevance when in co-occurrence with iridoids [97]. This was already observed in several species comprised in the Lamiales order [98][99][100][101][102][103] as well as in the case of several Pedicularis spp.Also within the same family which Pedicularis genus belong to (Orobanchaceae), these compounds are extremely common and, in fact, they have been already reported in several genera such as Orobanche L., Cistanche L. and Orthocarpus Nutt. [104].…”
Section: Chemotaxonomymentioning
confidence: 66%
“…Particularly, the HMBC crosspeak observed between δ 1.44 (Me-10) and 86.0 (C-8) was in agreement with the presence of a tertiary methyl group and a hydroxyl substituent geminally attached to C-8. The comparison of the NMR spectroscopic data with those reported in the literature ▶ for similar compounds [15] suggested that 1 possessed an ABX system in the cyclopentane ring, in which the methylene group at C-7 was adjacent to the oxygenated methine group at C-6, as in 6β-hydroxyipolamiide [16]. This assumption was confirmed by the HMBC correlations between H-6-C-8, H-6-C-9, and between H 2 -7-C-5, H 2 -7-C-8, and H 2 -7-C-9.…”
Section: Resultsmentioning
confidence: 96%
“…The chemical shifts observed for H-6 (δ H 4.38) and C-6 (δ C 74.9 ppm) in the HSQC spectrum indicated that C-6 was the position of esterification. The relative configuration of 1 was established on the basis of 1D NOESY data and comparison with the literature [15,17]. NOESY interactions between δ 1.44 (Me-10) and 6.19 (H-1), and between δ 1.44 (Me-10) and 4.38 (H-6) indicated the α-orientation of Me-10 and H-6, and the consequential β-orientation of 6-OCOCH 3 .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, compound ( 6 ), which is a derivative of apigenin with two saccharide residues, has been detected in the Lamiaceae family only in the genus Sideritis L. [ 40 , 41 ] and in other families such as Taxaceae [ 42 ], Caprifoliaceae [ 43 ], and Leguminosae [ 44 ]. Compound ( 8 ), which is a derivative of verbascoside with a further saccharidic residue (β-D-apiose), has been evidenced in the Lamiaceae family in the genus Phlomis L. [ 45 ] and in Teucrium chamaedrys L. [ 46 ], as well as in other families such as Orobanchaceae [ 38 ] and Verbenaceae [ 47 ]. On the above, also these compounds cannot be used as chemotaxonomic markers of M. incanum .…”
Section: Resultsmentioning
confidence: 99%